A separação de poderes na contemporaneidade: análise da atuação do STF a partir da sua estrutura institucional pós-1988 - Klein, Isabelle (2023)
This dissertation seeks to promote reflection on the problems of theory of the separation of powers and on the mechanisms for controlling the exercise of power. One of the biggest challenges to the tripartition of powers in Brazilian constitutionalism is, following a global trend, the leading role of the Judiciary. In this context, this expansion of jurisdiction was approached from two perspectives: from judicialization of politics and judicial activism. At this juncture, the research brought other challenges faced by the Separation of Powers in addition to Juristocracy that can lead to a democratic crisis, such as coalition presidentialism, party hyperfragmentation, polarized elections, media and strong public dissatisfaction society. Furthermore, the terms Supremocracy and Ministocracy were analyzed, which reveal that the institutional arrangement highlights the Federal Supreme Court in the arena politics, delimiting the causes that make him exercise the power of last word in the legal system and, often, in national politics. In this battle scenario of powers, the dynamics between the Powers during the pandemic were analyzed, especially the game of interests involving the Federal Executive Branch and the leadership of the Judicial Power. All this will lead, in the end, to the approach of dialogue theory institutions as a way of self-restraint by the Judiciary and as a new paradigm between the powers, in which dialogues are promoted involving both institutions of the democratic rule of law, as well as society. Therefore, the method used in this article is deductive, in addition to doctrinal and jurisprudence on the topic.